1987
DOI: 10.1038/325458a0
|View full text |Cite
|
Sign up to set email alerts
|

Gene structure and extracellular secretion of Neisseria gonorrhoeae IgA protease

Abstract: Several human bacterial pathogens, including the Gram-negative diplococcus Neisseria gonorrhoeae, produce extracellular proteases that are specific for human immunoglobulin IgA1. Immunoglobulin A (IgA) proteases have been studied extensively and the genes of some species cloned in Escherichia coli, but their role in pathogenesis remains unclear. Recently we derived a DNA fragment of 5 kilobases (kb) from N. gonorrhoeae MS11 directing extracellular active enzyme in E. coli. Although the mature enzyme of strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
559
4
5

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 609 publications
(583 citation statements)
references
References 27 publications
15
559
4
5
Order By: Relevance
“…Since the first description of IgA1 protease of N. gonorrhoeae by Pohlner et al (26), an increasing number of proteins have been discovered in various gram-negative organisms, which share the same mechanism of transportation, sometimes cess were then examined for the presence of the characteristic features of autotransporter proteins and for homology to known autotransporter proteins. We identified a novel putative autotransporter protein, which was designated AspA in view of its N-terminal homology to the autotransported serine proteases PrtT and PrtS, and their homologues, Ssp-H1 and Ssp-H2, in S. marcescens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first description of IgA1 protease of N. gonorrhoeae by Pohlner et al (26), an increasing number of proteins have been discovered in various gram-negative organisms, which share the same mechanism of transportation, sometimes cess were then examined for the presence of the characteristic features of autotransporter proteins and for homology to known autotransporter proteins. We identified a novel putative autotransporter protein, which was designated AspA in view of its N-terminal homology to the autotransported serine proteases PrtT and PrtS, and their homologues, Ssp-H1 and Ssp-H2, in S. marcescens.…”
Section: Discussionmentioning
confidence: 99%
“…AutB is probably a pseudogene (2). The autotransporter mechanism of protein transportation and secretion was first described for the immunoglobulin A1 (IgA1) proteases of pathogenic Neisseria (26) and is a rapidly expanding family of proteins (14,15). The characteristic structure of autotransporter proteins and the secretion mechanism have been reviewed elsewhere (15,17).…”
mentioning
confidence: 99%
“…1 Several labs have hypothesized that OM secretion of the passenger proceeds from C?N terminus. [10][11][12] In this scenario, extra stability at the C-terminus of the passenger might produce a folding template or nucleus that could promote the folding of the remainder of the b-helix during OM secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Early experiments in which the β domain was deleted showed that it plays an essential role in translocation and led to the proposal that it forms a channel through which the covalently linked passenger domain is secreted (15). Recently, however, several findings have challenged the "autotransporter" hypothesis.…”
mentioning
confidence: 96%